In Vivo Precision Evaluation of Lymphatic Function by SWIR Luminescence Imaging with PbS Quantum Dots. Issue 7 (1st January 2023) - Meng, Xinxian; Li, Huizhu; Chen, Yuzhou; Sai, Liman; Feng, Sijia; Li, Ke; Xi, Wenjing; Li, Yunxia; Thanh, Nguyen T. K.; Wang, Yueming; Wo, Yan; Yang, Xing; et al.
Abstract: Advancements in lymphography technology are essential for comprehensive investigation of the lymphatic system and its function. Here, a shortwave infrared (SWIR) luminescence imaging of lymphatic vessels is proposed in both normal and lymphatic dysfunction in rat models with PbS quantum dots (PbS Qdots). The lymphography with PbS Qdots can clearly and rapidly demonstrate the normal lymphatic morphology in both the tail and hind limb. More importantly, compared to ICG, SWIR luminescence imaging with PbS Qdots can easily identify the dominant lymphatic vessel and node with higher luminescence signal in rats. Moreover, lymphatic pump is identified as segment contracting sections with a size of ≈1 cm in rat by in vivo SWIR lymphograhy, which propose a direct feature for precise evaluation of lymphatic function. Notably, in vivo SWIR luminescence imaging with PbS Qdots also clearly deciphers the in vivo pattern of morphological and function recovery from lymphatic system in rat model. In summary, SWIR luminescence imaging with PbS Qdots can improve the lymphography and thus deepen the understanding of the morphology and structure of the lymphatic system as well as lymphatic function such as lymphatic pump, which will facilitate the diagnosis of lymphatic dysfunction in the future. Abstract : The shortwave infrared (SWIR) luminescence imaging with PbS quantum dots (PbS Qdots) is presented for the precise detection of lymphatic structure as well as the evaluation of lymphatic function represented by the lymphatic pump in both normal and pathological status, which will deepen the understanding of the lymphatic system and thus facilitate the diagnosis of lymphatic dysfunction in the future.